GOOD GOVERNANCE DARI PERSPEKTIF ILMU MANAJEMEN - I Gusti Ngurah Wairocana (Perspektif, 2006)
The term of corporate governance to come afer moneytary crisis in Asia particularly in East Asia. For Indonesian the concern of this term since monetary crisis moment which factually that there is a lack of good corporate governance force monetary crisis. Corporate governance has influenced greatly on companies, the board of directors, board of commissioners and shareholders in Indonesia. The stakeholders are now given wider opportunity with the adoption of corporate governance. Many sure this will add value to company sure nationalism. The existency of corporate governance was also to result in investor to invest the capital in a corporate which to comply with the principles of good corporate governance. For this, investor to have the guts to pay more the share in a corporate which to comply with the principles of good corporate governance. From management science perspective between management and good corporate governance in principe is the same, that are the process to run a corporation. But there are some different of both. Managemen just see inside of a corporation, good corporate not only see inside of a corporation but also see outside of a corporation likes supplier community buyer; environment and all of stakeholders. So the conclusion is good corporate governance more than good management.